(untitled) (Journal of Business and Technology (Dhaka), 2012)
The readymade garment RMG industry in Bangladesh has experienced an unprecedented growth .over the last three decades and become a fast growing industry in Bangladesh. This industry plays a vital role in the economy in terms of export earnings, employment generation ,poverty alleviation and empowering the woman. For development of this sector, Bangladesh needs to emphasize on the factory working environment, social issues, labor relations and compliances with codes of conduct. This paper is based on descriptive and inferential research. The paper suggests the improvement of factory activities through compliances and finds out a close relationship between compliance and productivity. DOI: http://dx.doi.org/10.3329/jbt.v5i2.9936 Journal of Technology (Dhaka) Vol. 5(2), July-December, 2010 71-87